The status of an X-ray mammography equipment park in the Russian Federation in 2011–2012 - A. D. Kaprin; N. I. Rozhkova; S. Yu. Mikushin (Вестник рентгенологии и радиологии)
Breast cancer is the first most common cancer among women. Its increasingly threatening trends force to search for ways to accelerate the introduction of current technologies for the early diagnosis and prevention of breast malignancies. The paper gives data on the quantity and distribution of diagnostic and minimally invasive mammography equipment by the regions of the Russian Federation, which may lead to the conclusion about the regions’ needs for equipment, trends, and possible prospects in the development of digital radiology in mammology.